Kenya Food Security Simulator (KFSS): Analyzing household data for food security insights - Mbuthia, Juneweenex; Omune, Lensa (CGIAR System Organization, 2023)
Recently, food security in the world has been heavily impacted by a series of complex crises calling for quick policy actions to respond to them. To inform such actions, innovative policy analysis tools are needed to not only inform but also guide policy direction when the crisis hits unexpectedly. It is in this view that Kenya Food Security Simulator (KFSS) has been jointly developed by Kenya Institute for Public Policy Research and Analysis (KIPPRA), Kenya National Bureau of Statistics (KNBS), and International Food Policy Research Institute (IFPRI) under the CGIAR initiative on National Policies and Strategies. The tool, designed in Excel, enables quick evaluations of direct household level outcomes of economic crises and policy responses in a timely manner. KFSS allows for a first-cut assessment of potential short-term impacts of food price or household income changes on food consumption, diet quality ,and other food security indicators among Kenya’s population groups.